KATEGORISASI EMOSI TOKOH UTAMA “NICKY” DALAM WINTER DREAMS KARYA MAGGIE TIOJAKIN: KAJIAN PSIKOLOGI SASTRA - Rahmah Purwahida (Pendidikan Bahasa dan Sastra Universitas Muhammadiyah Purworejo, 2020)
Abstract: The purpose of this study is to describe the emotional categorization of the main character in the novel Winter Dreams by Maggie Tiojakin based on David Krech's theory of emotional categorization with a literary psychology approach. The research method used is descriptive qualitative content analysis techniques. The validity and reliability of the data were obtained by semantic validity and triangulation with experts. The results of this study describe the findings of David Krech's emotional categorization of the main character